On the Electronic Origins of the Different Behaviors of S+ and S2+/2+ in Methane Activation. Issue 41 (30th October 2020) - Yu, Mincheng; Ruan, Jiancheng; Qian, Chao; Chen, Xinzhi; Ge, Xin; Zhou, Shaodong
Abstract: The thermal gas‐phase reactions of S +, S2 + and S2 2+ with methane have been explored by using quadrupole‐ion trap (Q‐IT) mass spectrometry complemented by quantum chemical calculations. In contrast to the reactiveness of the S + /CH4 and S2 2+ /CH4 couples as identified by experiment and computation, respectively, the S2 + /CH4 couple is inert at ambient temperature. Interestingly, the hydrogen‐atom transfer (HAT) prevails for S + /CH4 and proton‐coupled electron transfer (PCET) for S2 + /CH4, while both PCET and hydride transfer (HT) are accessible for S2 2+ /CH4 . Multiple factors matter for these processes. The electronic origins of the different reactivities of the three ions have been interrogated. Abstract : Rather different behaviors of the S +, S2 + and S2 2+ ions towards methane activation: efficient room‐temperature C−S coupling processes was identified experimentally for S + /CH4 ; in contrast, S2 + /CH4 was found inert under the same conditions; theory proved that the S2 2+ /CH4 couple is highly reactive. Hydrogen‐atom transfer (HAT) processes prevail for S + /CH4 and proton‐coupled electron transfer (PCET) for S2 + /CH4 ; for S2 2+ /CH4, though the PCET process is thermally accessible, an alternative hydride transfer (HT) step dominates.